2011
DOI: 10.1002/jbmr.399
|View full text |Cite
|
Sign up to set email alerts
|

Signal peptide mutations in RANK prevent downstream activation of NF-κB

Abstract: Familial expansile osteolysis and related disorders are caused by heterozygous tandem duplication mutations in the signal peptide region of the gene encoding receptor activator of NF-κB (RANK), a receptor critical for osteoclast formation and function. Previous studies have shown that overexpression of these mutant proteins causes constitutive activation of NF-κB signaling in vitro, and it has been assumed that this accounts for the focal osteolytic lesions that are seen in vivo. We show here that constitutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 25 publications
(58 reference statements)
3
30
0
Order By: Relevance
“…(5, 36, 37) In 2000, Hughes et al (5) reported that diminished cleavage of the signal peptide from FEO-RANK (84dup18) and PDB2-RANK (75dup27) led to intracellular sequestration of the mutated receptor and enhanced NF-κB signaling. In 2011, Crockett et al (36, 37) confirmed that FEO-RANK (84dup18), PDB2-RANK (75dup27), and ESH-RANK (84dup15) resist signal peptide cleavage, showed that these altered receptors localized differently within the organized smooth endoplasmic reticulum (perhaps somehow explaining the distinctive clinical phenotypes), and were unresponsive to extracellular RANKL. Additionally, they found that overexpression of these mutated RANKs would activate NF-κB, whereas physiologic levels did not enhance down-stream RANK signaling, including NF-κB.…”
Section: V) Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5, 36, 37) In 2000, Hughes et al (5) reported that diminished cleavage of the signal peptide from FEO-RANK (84dup18) and PDB2-RANK (75dup27) led to intracellular sequestration of the mutated receptor and enhanced NF-κB signaling. In 2011, Crockett et al (36, 37) confirmed that FEO-RANK (84dup18), PDB2-RANK (75dup27), and ESH-RANK (84dup15) resist signal peptide cleavage, showed that these altered receptors localized differently within the organized smooth endoplasmic reticulum (perhaps somehow explaining the distinctive clinical phenotypes), and were unresponsive to extracellular RANKL. Additionally, they found that overexpression of these mutated RANKs would activate NF-κB, whereas physiologic levels did not enhance down-stream RANK signaling, including NF-κB.…”
Section: V) Discussionmentioning
confidence: 99%
“…Additionally, they found that overexpression of these mutated RANKs would activate NF-κB, whereas physiologic levels did not enhance down-stream RANK signaling, including NF-κB. (36, 37) In fact, these altered RANKs, when homozygous, inactivated such signaling. Crockett et al (37) offered that in FEO, PDB2, and ESH perhaps mixed trimers of mutant and wild type RANK interacted somehow to enhance RANK activity, although the mechanism for the differing phenotypes remained unknown.…”
Section: V) Discussionmentioning
confidence: 99%
“…Subsequently, a duplication of 15 bp in the signal peptide region of RANK was found to be the cause of expansile skeletal hyperphosphatasia, another disease with clinical features that overlap to an extent with those of FEO and early-onset familial PDB [85,86]. These mutations prevent normal cleavage of the RANK signal peptide [83], and this causes the mutated RANK molecules to accumulate in the Golgi apparatus [87]. Although the mutated RANK molecules activate NF-jB signaling when overexpressed [83], cells that have been engineered to express a single copy of the mutant RANK show no evidence of a constitutive increase in NF-jB signaling, and they fail to initiate NF-jB or ERK responses to RANKL stimulation, indicating that these are loss-of-function mutations.…”
Section: Tnfrsf11amentioning
confidence: 96%
“…Although the mutated RANK molecules activate NF-jB signaling when overexpressed [83], cells that have been engineered to express a single copy of the mutant RANK show no evidence of a constitutive increase in NF-jB signaling, and they fail to initiate NF-jB or ERK responses to RANKL stimulation, indicating that these are loss-of-function mutations. Paradoxically, however, the mutant RANK molecules stimulate osteoclast formation in vitro when expressed in osteoclast precursors by mechanisms that remain incompletely understood [87].…”
Section: Tnfrsf11amentioning
confidence: 99%
“…Retroviral vectors have been extensively used by some research groups to transfect osteoclast precursors ( 1-3 ) but mature osteoclasts cannot be transfected with this technique since mitosis is required for integration of the retrovirus into the genome of the target cell. In this chapter, we describe methods for transfection of osteoclast precursors using lentiviral vectors (4)(5)(6) and the Amaxa™ Nucleofector ( 7 ) and also describe methods for transduction of mature osteoclasts using adenoviral vectors ( 8 ) , Fig. 1 illustrates the stages of osteoclast differentiation at which each technique is best employed.…”
mentioning
confidence: 99%